High-strength hard-tough aluminum-based composite material and preparation method thereof

By acidizing and dispersing chopped carbon fiber and boron carbide particles, combined with stir casting technology and heat treatment, the problem of difficulty in improving the hardness, strength and toughness of aluminum-based composite materials is solved, and the preparation of high-strength and tough aluminum-based composite materials is realized. , significantly improves its mechanical properties and service life.

CN119265492APending Publication Date: 2025-01-07WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411301956.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

It is difficult for existing aluminum-based composite materials to meet the requirements of hardness, strength and toughness at the same time, and the agglomeration between composite reinforcements leads to limited performance improvement.

Method used

By surface acidification of chopped carbon fiber and boron carbide particles and dispersing them in methyl cellulose solution, combining stirred casting process and heat treatment, the dispersion and surface binding force of the reinforced body in the composite material are improved, and high-quality products are prepared by combining high-quality products. Strong and tough aluminum-based composite material.

Benefits of technology

It effectively improves the hardness, strength and toughness of aluminum-based composite materials, extends its service life, reduces agglomeration and improves mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265492A_ABST
    Figure CN119265492A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength hard-tough aluminum-based composite material and a preparation method thereof.The preparation method comprises the following steps that chopped carbon fibers and boron carbide particles are subjected to surface acidizing treatment, then washed with water and dried, and acidized chopped carbon fibers and acidized boron carbide particles are obtained; the preparation method comprises the following steps: respectively dispersing acidified short carbon fibers and acidified boron carbide particles into a methylcellulose solution, filtering, washing with water, and drying to obtain pretreated short carbon fibers and pretreated boron carbide particles; pretreated short carbon fibers, pretreated boron carbide particles and metal mixed powder containing aluminum powder serve as raw materials, a high-strength hard-tough aluminum matrix composite precursor is obtained through a stirring casting technology, then heat treatment is conducted, and the high-strength hard-tough aluminum matrix composite is obtained. The mechanical properties such as tensile strength, yield strength, hardness and toughness of the material are improved by improving the dispersity and surface binding force of the compound reinforcement formed by the short carbon fibers and the boron carbide particles in the aluminum-based alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum-based composite materials, and in particular to a high-strength, hard-tough aluminum-based composite material and a preparation method thereof. Background Art

[0002] Aluminum-based composites have broad application prospects in aerospace, automotive, electronics and other fields due to their light weight, high strength and excellent corrosion resistance. In order to further extend the service life of aluminum-based composites, their mechanical properties need to be improved.

[0003] The commonly used method is to add a single reinforcement to the aluminum-based material. Although this method can meet certain specific performance requirements, it also has limitations. For example, it cannot simultaneously meet the material's requirements for hardness, strength and toughness. The use of composite reinforcements will face the problem of agglomeration between different reinforcements, and the resulting aluminum-based composite material still cannot meet the requirements.

[0004] Therefore, it is necessary to provide an aluminum-based composite material with a simple process, high dispersibility and excellent hardness, strength and toughness. Summary of the Invention

[0005] In view of this, the present application provides a high-strength, hard-tough aluminum-based composite material and a preparation method thereof, which are used to solve the problem of how to simultaneously improve the hardness and toughness of the aluminum-based composite material.

[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a method for preparing a high-strength, hard and tough aluminum-based composite material, comprising the following steps: S1. The chopped carbon fibers and boron carbide particles were surface-acidified, filtered, washed, and dried to obtain acidified chopped carbon fibers and acidified boron carbide particles; S2. The acidified chopped carbon fibers and the acidified boron carbide particles were dispersed in a methyl cellulose solution, filtered, washed, and dried to obtain pretreated chopped carbon fibers and pretreated boron carbide particles. S3. Using pretreated chopped carbon fibers, pretreated boron carbide particles, and a metal powder mixture containing aluminum powder as raw materials, a stir casting process was used to obtain a high-strength, tough, and aluminum-based composite material precursor; S4. Heat-treating the high-strength, hard-tough aluminum-based composite material precursor to obtain the high-strength, hard-tough aluminum-based composite material.

[0007] Preferably, the chopped carbon fibers are debonded fibers; the diameter of the chopped fibers is 5-10 μm, the length is 1-10 mm, and the tow is 3-6 K.

[0008] Preferably, the particle size D50 of the boron carbide particles is 1-10 μm.

[0009] Preferably, the metal mixed powder containing aluminum powder includes aluminum powder and composite powder, and the composite powder includes one or more of zinc powder, magnesium powder, copper powder, silicon powder, manganese powder, chromium powder, zirconium powder and titanium powder.

[0010] Preferably, in step S1, the surface acidification treatment step is: soaking the chopped carbon fibers and the boron carbide particles separately in a 60-70 g / L acid solution.

[0011] Preferably, the specific steps of step S3 are: heating and melting the metal mixed powder containing aluminum powder to obtain a molten liquid, cooling the molten liquid to a semi-solid range, and then adding pretreated short carbon fibers and pretreated boron carbide particles, stirring, and cooling to obtain a high-strength, hard-tough aluminum-based composite material precursor.

[0012] Preferably, the heating and melting temperature is 750-800°C, and the temperature range for cooling the melt to a semi-solid state is 600-650°C.

[0013] Preferably, the volume ratio of the pretreated chopped carbon fibers to the melt is 2.5-7.5:100, and the volume ratio of the pretreated boron carbide particles to the melt is 2.5-7.5:100.

[0014] Preferably, the heat treatment steps are: solution treatment at 470-500° C. for 2.5-3 h; and aging treatment at 145-160° C. for 12-16 h.

[0015] In a second aspect, the present application provides a high-strength, hard and tough aluminum-based composite material. The beneficial effects of the present application are as follows: The present invention improves the material strength by improving the dispersibility and surface bonding force of the composite reinforcement formed by chopped carbon fibers and boron carbide particles in the aluminum-based alloy, while effectively improving the hardness and toughness of the particle-reinforced aluminum-based composite material, thereby improving the mechanical properties such as hardness, strength and toughness of the aluminum-based composite material and increasing the service life of the aluminum-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the SEM image of the composite material obtained in Example 5. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0018] The present application provides a method for preparing a high-strength, hard-tough aluminum-based composite material, comprising the following steps: S1. The chopped carbon fibers and boron carbide particles were surface-acidified, filtered, washed, and dried to obtain acidified chopped carbon fibers and acidified boron carbide particles; S2. The acidified chopped carbon fibers and the acidified boron carbide particles were dispersed in a methyl cellulose solution, filtered, washed, and dried to obtain highly dispersed pretreated chopped carbon fibers and pretreated boron carbide particles. S3. Using pretreated chopped carbon fibers, pretreated boron carbide particles, and a metal powder mixture containing aluminum powder as raw materials, a stir casting process was used to obtain a high-strength, tough, and aluminum-based composite material precursor; S4. Heat-treating the high-strength, hard-tough aluminum-based composite material precursor to obtain the high-strength, hard-tough aluminum-based composite material.

[0019] In step S1 of the present application, the chopped carbon fibers and boron carbide particles are first subjected to acidification surface modification to increase surface activity, improve the interfacial bonding strength between the chopped carbon fibers and boron carbide particles and the aluminum matrix, and disperse them uniformly; in step S2, the chopped carbon fibers and boron carbide particles are respectively dissolved in methyl cellulose, which further promotes the dispersion of the two, improves the subsequent initial dispersibility of the carbon fibers and boron carbide particles in the molten aluminum-based composite material, and reduces agglomeration; the stirring casting process of step S3 is utilized to uniformly disperse the chopped carbon fibers and boron carbide particles into the aluminum-based metal, and then the mechanical properties are further enhanced through heat treatment in step S4 to obtain a high-strength, hard and tough aluminum-based composite material. It is worth noting that step S3 of the present application uses a stirring casting process, which can effectively disperse a single reinforcement evenly into the aluminum-based alloy. However, carbon fiber and boron carbide particles have agglomeration phenomenon. If the raw materials directly enter the stirring casting process, they will agglomerate in the initial state and be difficult to disperse, resulting in a negative impact on the hardness and / or toughness of the composite material. Therefore, the present application disperses the two reinforcements in the aluminum-based alloy melt through acid modification and methyl cellulose dissolution to overcome the above-mentioned defects; at the same time, the introduction and mixing of the two reinforcements, carbon fiber and boron carbide particles, enhance the hardness, tensile strength, yield strength and elongation at break of the composite material.

[0020] In some embodiments, the chopped carbon fiber is debonded fiber; the diameter of the chopped fiber is 5-10 μm and the length is 1-10 mm; the tow is 3-6 K; the chopped carbon fiber (chopped C f ) purchased from Jiangxi Shuobang New Material Technology Co., Ltd. It is a debonding raw material that requires no pretreatment and has a purity of 99.9%. The carbon fiber reinforcement, due to its high strength and modulus, can effectively improve the tensile strength and toughness of the composite material during pull-out and peeling.

[0021] In some embodiments, the boron carbide particles (B4C) have a particle size D50 of 1-10 μm. The boron carbide particles (B4C) used in this application were purchased from Zhongnuo New Materials Technology Co., Ltd. with a purity of 99.9%. The addition of boron carbide particles improves the hardness and wear resistance of the composite material.

[0022] In some embodiments, the metal mixed powder containing aluminum powder includes aluminum powder and composite powder, the composite powder includes one or more of zinc powder, magnesium powder, copper powder, silicon powder, manganese powder, chromium powder, zirconium powder, and titanium powder; the metal mixed powder containing aluminum powder is used to prepare aluminum-based alloy, wherein the content of aluminum powder is greater than or equal to 50%.

[0023] In some embodiments, in step S1 , the surface acidification treatment step is: soaking the chopped carbon fibers and the boron carbide particles separately in a 60-70 g / L acid solution.

[0024] Specifically, the operation of step S1 is: in a well-ventilated environment, the short-cut C f Soak the B4C particles in 60-70% concentrated nitric acid solution for 1-2 hours and stir; then chop the C f The B4C particles were taken out from the nitric acid solution and rinsed repeatedly with deionized water until the pH value of the rinse solution reached 7-7.4. The rinsed short-cut C f and B4C particles are placed in an oven and dried at 60-80° C. until completely dried to obtain acidified chopped carbon fibers and acidified boron carbide particles.

[0025] In some embodiments, the methylcellulose solution in step S2 is 5-10 g / L C 20 H 38 O 11 The aqueous solution is dispersed in the following way: the raw materials are soaked in the methyl cellulose solution for 10-20 minutes.

[0026] In some embodiments, the specific steps of step S3 are: heating and melting the metal mixed powder containing aluminum powder to obtain a molten liquid, cooling the molten liquid to a semi-solid range, and then adding pretreated chopped carbon fibers and pretreated boron carbide particles, stirring, and cooling to obtain a high-strength, hard and tough aluminum-based composite material precursor.

[0027] In some embodiments, the heating and melting temperature is 750-800°C, and the temperature range of the melt cooling to the semi-solid range is 600-650°C.

[0028] Specifically, step S3 is: heating the crucible of the smelting furnace to 750-800℃ for 15min, adding the metal mixed powder containing aluminum powder and melting it to obtain a molten liquid, naturally cooling it for 10min-15min to a semi-solid range, and then cooling it to a semi-solid range of 600-650℃, and then adding pretreated short carbon fiber and pretreated boron carbide particles according to the amount, stirring for 20min-30min, and cooling to obtain a high-strength, hard and tough aluminum-based composite material precursor.

[0029] In some embodiments, the volume ratio of the pretreated chopped carbon fibers to the melt is 2.5-7.5:100, and the volume ratio of the pretreated boron carbide particles to the melt is 2.5-7.5:100.

[0030] Preferably, the heat treatment temperature is solution treatment: 470° C.×2.5 h; aging treatment: 145° C.×12 h.

[0031] In a second aspect, the present application provides a high-strength, hard and tough aluminum-based composite material.

[0032] This application improves the material strength by improving the dispersibility and surface bonding force of the composite reinforcement, while effectively improving the plasticity of the particle-reinforced aluminum-based composite material, improving its mechanical properties such as tensile strength, hardness, and toughness, expanding its application range, and increasing its service life.

[0033] The present invention is further described below through specific examples.

[0034] Source of raw materials B4C particles: purchased from Zhongnuo New Materials Technology Co., Ltd., with a purity of 99.9%; average particle size of 1-10 μm; Short C f Purchased from Jiangxi Shuobang New Material Technology Co., Ltd., with a purity of 99.9%; the tow is 3K-6K; the diameter is 5-10μm; Metal mixed powder containing aluminum powder: purchased from Guangzhou Metal Metallurgy (Group) Co., Ltd., with a purity of 99.9%.

[0035] Example 1 A method for preparing a high-strength, hard-tough aluminum-based composite material comprises the following steps: S1. Under ventilation, 36.84 g of chopped carbon fiber (3K tow) and 51.57 g of boron carbide particles were immersed in a 60% by mass nitric acid solution for 1 h with stirring. The mixture was then removed and repeatedly rinsed with a large amount of deionized water until the pH of the rinse solution reached 7. The rinsed materials were then dried in an oven at 60°C until completely dry to obtain acidified chopped carbon fiber and acidified boron carbide particles. S2. Disperse the acidified chopped carbon fibers and acidified boron carbide particles into 5 g / L C 20 H 38 O 11 The mixture was immersed in the aqueous solution for 20 minutes and stirred, filtered, washed with deionized water, and dried at 60°C to obtain pretreated chopped carbon fibers and pretreated boron carbide particles. S3. The crucible of the melting furnace is heated to 750°C for 15 minutes, and a total mass of 1167.57g of metal mixed powder (including 1057.84 parts of pure aluminum powder, 59.54 parts of zinc powder, 24.51 parts of magnesium powder, 14.01 parts of copper powder, silicon powder, manganese powder, chromium powder, zirconium powder, and titanium powder totaling 11.67 parts) is placed in the crucible of the melting furnace and heated to melt to obtain a melt, which is naturally cooled for 5 minutes to a semi-solid range of 650°C, and then 5vt% of the melt of pretreated chopped carbon fibers and 5vt% of the melt of pretreated boron carbide particles are added, stirred for 20 minutes, and cooled to obtain a high-strength, hard-tough aluminum-based composite material precursor; S4. Heat treatment of the high strength and toughness aluminum matrix composite precursor: solution treatment: 470℃×2.5h; aging treatment: 145℃×12h, to obtain high strength and toughness aluminum matrix composite (5V%C f / 5V% B4C / Al).

[0036] Example 2 A method for preparing a high-strength, hard-tough aluminum-based composite material comprises the following steps: S1. Under ventilation, 77.48 g of chopped carbon fiber (tow 3K) and 18.44 g of boron carbide particles were immersed in a 60% by mass nitric acid solution for 1 h with stirring. The mixture was then removed and repeatedly rinsed with a large amount of deionized water until the pH of the rinse solution reached 7. The rinsed materials were then dried in an oven at 60°C until completely dry to obtain acidified chopped carbon fiber and acidified boron carbide particles. S2. Disperse the acidified chopped carbon fibers and acidified boron carbide particles into 5 g / L C 20 H 38 O 11 The obtained carbon fibers were immersed in the aqueous solution for 20 minutes with stirring, washed with deionized water and dried at 60°C to obtain pretreated chopped carbon fibers and pretreated boron carbide particles. S3. The crucible of the melting furnace is heated to 750°C for 15 minutes, and a total mass of 1168.32g of metal mixed powder (including 1058.51 parts of pure aluminum powder, 59.58 parts of zinc powder, 24.53 parts of magnesium powder, 14.02 parts of copper powder, silicon powder, manganese powder, chromium powder, zirconium powder, and titanium powder totaling 11.68 parts) is placed in the crucible of the melting furnace and heated to melt to obtain a melt, which is naturally cooled for 5 minutes to a semi-solid range of 650°C, and then 2.5vt% of the melt of pretreated chopped carbon fibers and 7.5vt% of the melt of pretreated boron carbide particles are added, stirred for 20 minutes, and cooled to obtain a high-strength, hard-tough aluminum-based composite material precursor; S4. Heat treatment of the high strength and toughness aluminum matrix composite precursor: solution treatment: 470℃×2.5h; aging treatment: 145℃×12h, to obtain high strength and toughness aluminum matrix composite (2.5V%C f / 7.5V% B4C / Al).

[0037] Example 3 A method for preparing a high-strength, hard-tough aluminum-based composite material, the other contents are the same as those in Example 1, except that in step S3, the step of naturally cooling for 5 minutes to a semi-solid range of 650°C is replaced by naturally cooling for 10 minutes to a semi-solid range of 600°C.

[0038] Example 4 A method for preparing a high-strength, hard-tough aluminum-based composite material, the other contents of which are the same as those of Example 1, except that in step S3, the stirring time of 20 minutes is replaced by 30 minutes.

[0039] Example 5 A method for preparing a high-strength, hard-tough aluminum-based composite material, the other contents of which are the same as those of Example 3, except that the tow of the chopped carbon fiber is 6K.

[0040] Comparative Example 1 A method for preparing a high-strength, hard-tough aluminum-based composite material, the other contents of which are the same as those of Example 1, except that step S2 is not included.

[0041] Comparative Example 2 A method for preparing a high-strength, hard-tough aluminum-based composite material, the other contents of which are the same as those of Example 1, except that step S1 is not included.

[0042] Testing and Evaluation The prepared samples were wire-cut into test specimens for the required tests, and the hardness and mechanical properties of the aluminum-based composite materials obtained in each embodiment and comparative example were tested using a Vickers hardness tester and a universal testing machine. The results are shown in Table 1, where the aluminum alloy prepared using the metal mixed powder in Example 1 as raw material is used as the control example.

[0043] Table 1 Mechanical properties of samples obtained in various examples

[0044] As shown in Table 1, the highly dispersed short-cut C prepared in Examples 1 to 5 f The hardness and tensile strength of the aluminum-based composite material reinforced by mixing with B4C particles are greater than those of the matrix material aluminum alloy, and the yield strength is maintained at a high level. The composite material has good strength. In addition, the elongation at break is maintained at about 8%, and the fracture toughness of the composite material is excellent, indicating that the present invention greatly improves the mechanical properties and hardness of the aluminum alloy, and expands the performance research and application scope of the aluminum-based composite material.

[0045] The aluminum-based composite material obtained in Example 5 was subjected to SEM analysis. Figure 1 As shown, Figure 1 (a) The carbon fibers, boron carbide particles, and aluminum matrix are tightly bonded. Figure 1 (b) The backscattered image also shows good wettability of the interface. Figure 1 (c) Figure 1 (d) Carbon fibers and boron carbide particles are uniformly dispersed in the aluminum matrix at low magnification, and the carbon fibers are interwoven in the matrix. The highly dispersed chopped C prepared in Example 5 f The aluminum matrix composite material reinforced by mixing with B4C particles has excellent hardness, tensile strength and elongation at break. The parameters are initial raw material (tow): 6K-C f 、Volume fraction: 5V%C f / 5V% B4C, semi-solid melting temperature: 600℃, C f and B4C particles are evenly dispersed in the aluminum matrix, and a C f A high-hardness and toughness aluminum-based composite material reinforced by mixing with B4C particles and a preparation method thereof.

[0046] The above are only preferred specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or replacements that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.

Claims

1. A method for preparing a high-strength, hard and tough aluminum-based composite material, characterized in that: The following steps are involved: S1. The chopped carbon fibers and the boron carbide particles are subjected to surface acidification treatment, respectively, and then washed and dried to obtain acidified chopped carbon fibers and acidified boron carbide particles; S2. The acidified chopped carbon fibers and the acidified boron carbide particles are dispersed in a methyl cellulose solution, respectively, and after filtering, washing, and drying, corresponding pretreated chopped carbon fibers and pretreated boron carbide particles are obtained; S3. Using the pretreated chopped carbon fiber, pretreated boron carbide particles and metal mixed powder containing aluminum powder as raw materials, a stirring casting process is used to obtain a high-strength and tough aluminum-based composite material precursor; S4. heat-treating the high-strength and toughness aluminum-based composite material precursor to obtain the high-strength and toughness aluminum-based composite material.

2. The method for preparing the high-strength, hard-tough aluminum-based composite material according to claim 1, characterized in that: The chopped carbon fibers are degummed fibers; the diameter of the chopped fibers is 5-10 μm, the length is 1-10 mm, and the tow is 3-6 K.

3. The method for preparing the high-strength, hard-tough aluminum-based composite material according to claim 1, characterized in that: The particle size D50 of the boron carbide particles is 1-10 μm.

4. The method for preparing the high-strength, hard-tough aluminum-based composite material according to claim 1, characterized in that: The metal mixed powder containing aluminum powder includes aluminum powder and composite powder, and the composite powder includes one or more of zinc powder, magnesium powder, copper powder, silicon powder, manganese powder, chromium powder, zirconium powder and titanium powder.

5. The method for preparing a high-strength, hard-tough aluminum-based composite material according to claim 1, characterized in that: In step S1, the surface acidification treatment step is: soaking the chopped carbon fibers and boron carbide particles in 60-70 g / L acid solution respectively.

6. The method for preparing a high-strength, hard-tough aluminum-based composite material according to claim 1, characterized in that: The specific steps of step S3 are: heating and melting the metal mixed powder containing aluminum powder to obtain a molten liquid, cooling the molten liquid to a semi-solid range, and then adding the pretreated chopped carbon fibers and pretreated boron carbide particles, stirring and cooling, to obtain the high-strength, hard and tough aluminum-based composite material precursor.

7. The method for preparing a high-strength, hard-tough aluminum-based composite material according to claim 6, characterized in that: The heating and melting temperature is 750-800°C, and the temperature range of the molten liquid to cool to a semi-solid range is 600-650°C.

8. The method for preparing a high-strength, hard-tough aluminum-based composite material according to claim 6, characterized in that: The volume ratio of the pretreated chopped carbon fibers to the melt is 2.5-7.5:100, and the volume ratio of the pretreated boron carbide particles to the melt is 2.5-7.5:

100.

9. The method for preparing a high-strength, hard-tough aluminum-based composite material according to claim 1, characterized in that: The heat treatment steps are: solution treatment at 470-500°C for 2.5-3h; aging treatment at 145-160°C for 12-16h.

10. A high-strength, hard-tough aluminum-based composite material obtained by the preparation method according to any one of claims 1 to 9.